Investigating the Use of Comic Strips Media on Developing Students' Narrative Writing Skills: A Case Study in Language Teaching - Elina Lulu Bimawati Rumapea; Ruty Jacoba Kapoh; Chatarina Novianti; Yuniarsih Yuniarsih; Indah Permata Sari Harita; Herman Herman; Nanda Saputra (STAI Hubbulwathan Duri, 2025)
Eighth-grade EFL students often struggle with narrative writing due to unstructured ideas, limited vocabulary, and disengagement with traditional teaching methods. To address this, the study explores the use of comic strips as a visual and interactive instructional tool to enhance narrative writing skills. This quasi-experimental study used a non-equivalent pre-test and post-test control group design. Sixty purposively selected students were divided into experimental and control groups. The experimental group was taught narrative writing using comic strips, while the control group received conventional instruction. A 20-item narrative writing test was administered before and after the intervention. Data were analyzed through validity and reliability checks, tests for normality and homogeneity, and hypothesis testing using either an independent t-test or Mann–Whitney U test, depending on the data distribution. The experimental group showed statistically significant improvements in narrative writing performance, particularly in idea development, coherence, and creativity. The control group displayed only marginal progress. These results suggest that comic strips effectively support the organization of narrative structure and enhance expression. The findings underscore the pedagogical value of comic strips as a multimodal instructional medium. Their visual nature facilitates idea generation and supports narrative coherence, leading to more confident and creative student writing. Comic strips can be a valuable addition to EFL writing instruction. Teachers are encouraged to integrate this medium to improve students’ narrative writing skills and overall engagement.